2020
DOI: 10.1097/wnf.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate-Induced Enuresis: 3 Case Reports

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder in children and adolescents. Methylphenidate (MPH) is one of the most widely used drugs in the treatment of ADHD. Enuresis can occur comorbidly with ADHD. However, enuresis is sometimes seen in patients with ADHD as an adverse effect of MPH treatment. In contrast, in some cases, MPH reportedly improves enuresis in patients with ADHD comorbid with enuresis. The literature is contradictory with regard to the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…We found that about one in ten children had a 20% or greater increase in HR, sBP, or dBP in the 3 h following the initial dose, and that about one in five had a similar increase after 1 week of treatment. These data indicate a lack of tolerance to the cardiovascular effects of MPH, at least in the short-term, and are consistent with the conclusions of previous reports [ 1 , 16 ]. One patient (0.2%) had sustained tachycardia, without subjectively reported palpitations, in the first 3 hours after first MPH dosing with 10 mg.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that about one in ten children had a 20% or greater increase in HR, sBP, or dBP in the 3 h following the initial dose, and that about one in five had a similar increase after 1 week of treatment. These data indicate a lack of tolerance to the cardiovascular effects of MPH, at least in the short-term, and are consistent with the conclusions of previous reports [ 1 , 16 ]. One patient (0.2%) had sustained tachycardia, without subjectively reported palpitations, in the first 3 hours after first MPH dosing with 10 mg.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with existing literature on tics and stimulant medications [ 15 ]. A small number of children (14 or 2.9%) reported enuresis, which is not an adverse event typically associated with stimulant treatment, even though it has been anecdotally reported [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon our review of the literature and as in our patient, it appears that enuresis develops in a dose-dependent fashion 8–11 . It is postulated that, at higher doses, MPH antagonizes α1 adrenergic receptors 12 in the internal urethral sphincter producing urinary incontinence by decreasing the sphincter pressure 7 (please see Table 1 for a list of the cases of MPH-induced enuresis).…”
Section: Discussionmentioning
confidence: 55%
“…4 Although there are studies in the literature showing that methylphenidate is effective in the treatment of enuresis accompanying ADHD, cases of enuresis occurring during the use of methylphenidate have been reported, albeit rarely. [7][8][9][10][11] In our case, immediate-release methylphenidate (10 mg and 20 mg) and ER-MPH (27 mg and 36 mg) were used after diagnosis in the past years, but enuresis did not develop. It was learned from the information obtained from the parents and the school that the patient had a moderate improvement in ADHD symptoms when he was last used ER-MPH (36 mg).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation